Improved Monitoring Performance of Financial Trading Algorithms Using a Graphical Display. (September 2018) - Li, Yeti; Wang, Xian; Burns, Catherine M.
Ecological Interface Design (EID) has been applied to financial trading to derive graphical forms from work analysis models to improve monitoring performance. Automated trading requires contextual support for monitoring algorithm failures, and we designed a graphical, hybrid display inspired by EID to provide such support. We report a two-stage experiment involving a pilot study and a formal study to evaluate the hybrid display with participants who have a basic understanding of computer algorithms. The pilot study used an initial version of the trading algorithm. The formal study used similar apparatus but a modified algorithm. Results showed that the hybrid display provided better support than the conventional display for detecting algorithm failures only when the contextual support provided by the conventional and the representational visualizations was consistent. Further, we discuss the compatibility issue in designing hybrid displays.